Integration of Digital Storytelling in Project-Based Learning: A Systematic Literature Review - Sarah Setianingsih; Didin Saripudin (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Limited student engagement, passive teaching patterns, and underdeveloped historical thinking skills pose challenges to history learning. Therefore, in the context of rapid digital transformation, innovative, student-centered pedagogies are essential to create meaningful learning experiences. However, technology integration often remains confined to technical implementation, lacking a robust pedagogical framework. This study aims to identify, examine, and synthesize the usage patterns, impacts, challenges, and opportunities associated with the integration of digital storytelling within project-based history learning. Employing a Systematic Literature Review (SLR) methodology, this research synthesizes findings from 14 articles sourced from Scopus and Web of Science, with Google Scholar utilized as a supplementary database, covering publications from 2019 to 2025. The reviewed literature indicates that digital storytelling functions as an integrated meaning-making tool, spanning from source exploration to historical reflection. The findings show that the integration of digital storytelling in project-based history learning supports students’ historical understanding, engagement, digital literacy, and historical empathy through contextual and reflective learning processes. However, successful implementation depends not only on technological infrastructure but also on teachers’ pedagogical readiness and instructional scaffolding. The implications of this study emphasize that the integration of project-based learning and digital storytelling requires a shift from technical mastery toward structured pedagogical support to facilitate meaningful history learning in the digital era.